Factor: 3x4y3 – 48y3. ???
Answers
Answered by
11
Answer:
Step-by-step explanation:
Solution:
3x4y3– 48y3.
= 3y3(x4 – 16).
= 3y3[(x2)2 - 42].
= 3y3(x2 + 4)(x2 - 4).
= 3y3(x2 + 4)(x2 - 22).
= 3y3(x2 + 4)(x + 2)(x -2).
Answer: 3y3(x2 + 4)(x + 2)(x -2)
Answered by
2
hope this will help you and marks it as brainlist plzzzzzzzzz also follow me guys.
Attachments:
![](https://hi-static.z-dn.net/files/db6/29db68735dc42693ad6870d1c197e513.jpg)
![](https://hi-static.z-dn.net/files/db9/76abe257635da9eb015f8f1beecd1d62.jpg)
Similar questions
Social Sciences,
5 months ago
Accountancy,
5 months ago
Biology,
10 months ago
Social Sciences,
10 months ago
Physics,
1 year ago